SENI, DESAIN DAN KEBUDAYAAN DALAM SPIRIT REVOLUSI INDUSTRI 4.0 - Amir Piliang, Yasraf (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
The arrival of the fourth wave of the industrial revolution, called the Industrial Revolution 4.0, which was supported by the development of digital information technology, has influenced the development of art, design and culture. At least, there are three main factors that influence this development. First, the development of digital information technology, and "digitalization" of almost all sectors of life, especially economic and industrial aspects. Second, the development of a network society, which makes networking work as the main way of working today. Third, the development of the workings of collaboration, as a logical consequence of the development of networking communities. This study aims to reveal the influence of these three main factors in the development of art, design and culture. The study shows the development of the Industrial Revolution 4.0, the power of digital networks and networking communities, the growth of the Internet of Things (IoT) and other modern digital information technologies, the phenomenon of technological disruption, the power of destruction of innovation, and the role of art and design in creating disruptive ideas, understood as an inseparable and interrelated unity. Everything must be understood as a set of interrelated and interconnected phenomena, which if they fail to understand one causes failure in understanding the other. Through comprehensive and integrated understanding, a "big picture" can be described about what radical changes and fundamentals are taking place.